SO42−/ZrO2 as catalyst for upgrading of pyrolysis oil by esterification. (15th August 2018) - Li, Lu; Yan, Bin; Li, Huaxiao; Yu, Shitao; Liu, Shiwei; Yu, Hailong; Ge, Xiaoping
Abstract: Pyrolysis oil of rubber seed oil (RSO) was upgraded by methyl esterificationusingSO4 2− /ZrO2 solid acid as catalyst. The activity and reusability of SO4 2− /ZrO2 solid acid were investigated and the experiment indicated that the esterification rate could reach 99.62% and was still above 95% in the third reaction. The component of SO4 2− /ZrO2 solid acid changed little after the third used. The properties of the obtained biofuel were studied and the results showed they were superior to pyrolysis oil and biodiesel, and similar to 0 # diesel. The methyl esterification reaction kinetics was researched. The kinetics calculation indicated that the reaction order of the methyl esterification is 1.058, and Arrhenius equation can be expressed as k 1 = 7.711 × 10 6 e - 47.913 RT .